(untitled) (IUBAT Review, 2023)
Study on soil erosion in the coastal region of Bangladesh is crucial due to its severe environmental and socio-economic impacts. Understanding erosion patterns, identifying vulnerable areas, and developing effective conservation strategies are essential to safeguard agricultural productivity, preserve coastal ecosystems, and protect the livelihoods of coastal communities. This study focuses on soil erosion in the low-lying, flood-prone coastal regions of Bangladesh. The Revised Universal Soil Loss Equation (RUSLE) technique was used to calculate soil erosion rates. The southern section of the study area, characterized by high rainfall erosivity (R) and soil erodibility (K), exhibited the highest erosion rates at 1446 t/ha/year. The region experiences significantly higher rainfall erosivity than other parts of the world. Cox’s Bazar, Chittagong, Feni, and Patuakhali receive over 3000 mm/yr of precipitation, while Teknaf and Hatiya surpass 4000 mm/yr. The vulnerability of the soft, sand-rich topsoil to water-driven gully and rill erosion contributes to the high erodibility factor. Conversely, the northwest and low-lying marshy areas exhibit low erosion rates due to the flat terrain and deposition of eroded soil mass from the hinterland. The hilly areas of Chittagong, Teknaf, and Cox’s Bazar experience above-average erosion rates. Effective soil conservation and management strategies are essential for reducing soil erosion in Bangladesh’s coastal regions, considering local environmental conditions such as precipitation and soil type. The findings of this research provide valuable insights for future studies and policies on soil erosion management in the coastal districts of Bangladesh. By guiding efficient conservation efforts, this information can help mitigate the adverse impacts of soil erosion on the environment and economy. IUBAT Review, 6(2): 1-24